Government subsidies and income smoothing - Pappas, Kostas; Walker, Martin; Xu, Alice Liang; (Colin) Zeng, Cheng (Contemporary accounting research, 2024)
This study examines the relationship between government subsidies and income smoothing using a sample of US‐listed firms. We find that subsidized firms smooth their earnings more aggressively than their unsubsidized peers. This finding is consistent with the reasoning that subsidized firms bear higher political costs and have more incentives to smooth earnings to avoid public attention. In addition, smoothing by subsidized firms is more pronounced when the subsidies are granted through non‐tax‐related channels than through tax‐based channels, and the positive association between government subsidies and income smoothing is stronger for firms under higher public scrutiny and with less transparent information environments. Further analysis shows that smoothing by subsidized firms serves mainly to obfuscate earnings and that subsidized firms that smooth earnings tend to continue receiving subsidies in the future. Overall, our results help explain the role of government subsidies in shaping firms' accounting and disclosure choices. Résumé Subventions gouvernementales et lissage des résultats Cette étude examine la relation entre les subventions gouvernementales et le lissage des résultats à partir d'un échantillon d'entreprises cotées en bourse aux États‐Unis. Le travail d'analyse démontre que les entreprises subventionnées lissent leurs résultats de manière plus intensive que leurs homologues non subventionnées. Ce résultat appuie l'idée que les entreprises subventionnées assument des conséquences politiques plus lourdes et sont davantage motivées à lisser leurs résultats pour dévier l'attention du public. En outre, le lissage est plus prononcé chez les entreprises subventionnées lorsque les subventions sont accordées dans un cadre non fiscal, comparativement à un cadre fiscal. Par ailleurs, la relation positive entre les subventions gouvernementales et le lissage des résultats est plus forte pour les entreprises soumises à un contrôle public accru et dont l'environnement informationnel favorise moins la transparence. Une analyse plus approfondie révèle que le lissage pratiqué par les entreprises subventionnées vise principalement à maquiller les résultats et que ces entreprises ont tendance à recevoir de nouvelles subventions dans le futur. En résumé, cette étude contribue à expliquer le rôle des subventions gouvernementales dans les décisions des entreprises en matière de comptabilité et de communication d'informations.